STRATEGI PENINGKATAN FASILITAS DI PELABUHAN PERIKANAN LAMBADA LHOK, ACEH BESAR - Muklis, Muklis; Rizqi, Miftahul; Kurnia, Kurnia (JURNAL PERIKANAN TROPIS, 2025)
The Lambada Lhok Fish Landing Base (PPI Lambada Lhok), strategically located in Aceh Besar District, serves as an important fisheries port. However, its current infrastructure remains insufficient to support optimal fishing activities. This study aimed to develop strategic recommendations for improving the facilities and operational performance of PPI Lambada Lhok. Primary data were collected through direct observation, questionnaires, and semi-structured interviews with purposively selected stakeholders. Secondary data, encompassing fishing gear inventories, landing volumes, fleet composition, and existing infrastructure, were obtained from the port management authority. Data were analysed using SWOT analysis, followed by prioritization of strategic alternatives through the Quantitative Strategic Planning Matrix (QSPM). The QSPM results identified three priority strategies: (1) dredging the port basin to maintain adequate navigational depth and ensure smooth vessel operations (TAS = 5.969); (2) increasing the number of fishing vessels above 5 gross tonnes (GT) to enhance fleet capacity (TAS = 5.598); and (3) upgrading port facilities to support increased production of key fishery commodities, leveraging the resource potential of Fisheries Management Areas (WPP-NRI) 571 and 572 (TAS = 5.562). Implementation of these prioritized strategies is strongly recommended to port authorities and relevant stakeholders to accelerate the development and operational efficiency of PPI Lambada Lhok